Preparation method and application of self-crosslinking hydrogel containing capsaicin functional structure

By introducing capsaicin functional monomers and cross-linking agents into hydrogels, a self-cross-linking hydrogel with multiple adsorption sites was constructed. Through pre-oxidation and carbonization treatment, the problems of simple hydrogel material structure and difficulty in recycling were solved, achieving efficient adsorption and environmentally friendly dye removal.

CN121021741APending Publication Date: 2025-11-28SANYA INST OF OCEANOGRAPHY OCEAN UNIV OF CHINA
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511539528.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-27
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing hydrogel materials have a simple structure and insufficient effective adsorption sites for crosslinking agents, making recycling difficult, resulting in low adsorption efficiency and the potential introduction of secondary pollution.

Method used

By introducing capsaicin functional structural monomers and preparing crosslinking agents through Friedel-Crafts alkylation reaction, and combining them with acrylic acid, polyhydroxybenzoic acid and sulfonic acid benzenesulfonic acid monomers, a self-crosslinking hydrogel with multiple adsorption sites is constructed by free radical polymerization, and the material properties are improved by pre-oxidation and carbonization treatment.

Benefits of technology

It significantly improves the adsorption capacity and efficiency of hydrogels, avoids secondary pollution during acid/alkali desorption, and achieves efficient recycling of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121021741A_ABST
    Figure CN121021741A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of self-crosslinking hydrogel containing a capsaicin functional structure, and belongs to the technical field of dye adsorption materials. The capsaicin functional structure monomer is introduced into an acrylic acid system, so that the self-crosslinking of the hydrogel is realized, and meanwhile, the adsorption performance of the hydrogel is remarkably improved; mono-substituted capsaicin functional structure monomers containing carboxyl and sulfonic acid groups are used as components, a disubstituted capsaicin functional structure monomer with polyhydroxy and carboxyl is used as a cross-linking agent, the self-crosslinking hydrogel with multiple adsorption sites is successfully constructed through free radical polymerization, and the adsorption capacity and efficiency of the hydrogel are greatly improved. The hydrogel-based carbon material is obtained by carbonizing the self-crosslinking hydrogel containing the capsaicin functional structure, the adsorption performance of the hydrogel material is further improved, the obtained hydrogel-based carbon material can be desorbed and recycled in ethyl alcohol, and the service life of the hydrogel-based carbon material is prolonged. And the problem of secondary pollution of the existing hydrogel material in the acid / alkali desorption process is effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of dye adsorption materials technology, and particularly relates to a method for preparing and applying a self-crosslinking hydrogel containing capsaicin functional structure. Background Technology

[0002] Wastewater containing highly toxic, non-biodegradable, and carcinogenic organic dyes is considered a serious threat to the ecological environment and human health. Currently, technologies such as adsorption, ion exchange, photocatalysis, membrane filtration, and electrochemistry are widely used to remove harmful dyes from wastewater. Among these, adsorption technology is widely adopted due to its advantages of simple operation and low cost. However, traditional adsorbents such as silica and activated carbon often face problems such as low treatment efficiency and difficulty in separation. Therefore, developing environmentally friendly materials with high adsorption capacity and recyclability has become an important research direction.

[0003] Hydrogels are considered one of the most efficient adsorbent materials due to their excellent biocompatibility, biodegradability, non-toxicity, and operational safety. Among the methods for preparing hydrogels, chemical copolymerization and crosslinking technology is widely used because of its simple synthesis process, stable structure, and high thermal and chemical stability.

[0004] However, hydrogel materials still face several limitations in practical applications. When using single monomers such as acrylic acid and acrylamide as the main reactants, the types and numbers of functional groups they contain are limited, making it difficult to achieve multifunctional synergistic adsorption. Commonly used chemical crosslinking agents, such as N,N'-methylenebisacrylamide and polyethylene glycol diacrylate, while imparting excellent stability to hydrogels, lack active sites that can interact with dyes, thus limiting adsorption efficiency. More importantly, most hydrogels require desorption and regeneration with strong acid or alkali solutions after adsorption, which not only damages the material structure and active functional groups, causing adsorption performance degradation, but may also introduce secondary pollution problems. In summary, the problems of existing hydrogel materials, such as simple structural composition, insufficient effective adsorption sites of crosslinking agents, and difficulties in recycling, seriously limit their processing performance and large-scale application. Summary of the Invention

[0005] To address the technical problems of existing hydrogel materials, such as monotonous structural composition, insufficient effective adsorption sites for crosslinking agents, and difficulties in recycling, this invention proposes a method for preparing and applying a self-crosslinking hydrogel containing capsaicin functional structures.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] This invention provides a capsaicin-containing self-crosslinking hydrogel, the structural formula of which is:

[0008] ;

[0009] R1, R2, R3, and R4 are independently selected from H, -OH, or -COOH; x is 2 to 10, y is 20 to 100, and z is 2 to 10.

[0010] Technical Principle: This invention introduces capsaicin functional monomers into an acrylic acid system. These functional monomers, derived from natural capsaicin, inherit the advantages of non-toxicity and abundant active groups found in natural capsaicin. While achieving self-crosslinking of the hydrogel, they significantly enhance its adsorption performance. Using monosubstituted capsaicin functional monomers containing carboxyl and sulfonic acid groups as components, and disubstituted capsaicin functional monomers with both polyhydroxy and carboxyl groups as crosslinking agents, a self-crosslinking hydrogel with multiple adsorption sites is successfully constructed through free radical polymerization, greatly improving the hydrogel's adsorption capacity and efficiency. Simultaneously, the hydrophilic monomer (acrylic acid / monosubstituted capsaicin monomer) and the multifunctional (disubstituted capsaicin monomer) crosslinking agent form a three-dimensional polymer network linked by covalent bonds through free radical polymerization, achieving self-crosslinking of the hydrogel.

[0011] This invention provides a method for preparing the capsaicin-containing self-crosslinking hydrogel described in the above technical solution, comprising the following steps:

[0012] (1) Dissolve acidic aromatic compounds and N-hydroxymethylacrylamide in an organic solvent, then add concentrated sulfuric acid dropwise, and obtain a crosslinking agent (CSCA) with capsaicin functional structure through Friedel-Crafts alkylation reaction.

[0013] (2) Acrylic acid (AA), 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid (TA) and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid (SA) are dissolved in water, and then the neutralization degree of the solution is adjusted. Then an initiator and a crosslinking agent of the capsaicin functional structure are added, and the mixture is reacted in a water bath to obtain the capsaicin-containing self-crosslinking hydrogel (AA / TA / SA@CSCA).

[0014] Further, in step (1), the acidic aromatic compound is selected from 2,4-dihydroxybenzoic acid (24DA), 2,6-dihydroxybenzoic acid (26DA), 3,5-dihydroxybenzoic acid (35DA), gallic acid (345TA) or pyrogallic acid (456TA).

[0015] Further, in step (1), the molar ratio of the acidic aromatic compound and N-hydroxymethylacrylamide is 1:(2~3).

[0016] Furthermore, in step (1), the temperature of the Friedel-Crafts alkylation reaction is 35~40℃, and the time of the Friedel-Crafts alkylation reaction is 2~4 days.

[0017] Further, in step (2), the molar ratio of acrylic acid, 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid is 20:(0.5~1.5):(0.3~0.7); the amount of crosslinking agent added to the capsaicin functional structure is 0.15%~0.25% of the total molar amount of acrylic acid, 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid; and the amount of initiator added is 0.04%~0.06% of the total molar amount of acrylic acid, 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid.

[0018] Furthermore, in step (2), the temperature of the water bath reaction is 65~75℃, and the time of the water bath reaction is 2.5~3.5 hours.

[0019] The present invention also provides a capsaicin-containing functional structure self-crosslinking hydrogel-based carbon material (C-AA / TA / SA@CSCA), which is obtained by pre-oxidation and carbonization treatment of the capsaicin-containing functional structure self-crosslinking hydrogel described in the above technical solution.

[0020] Further, the pre-oxidation temperature is 180~220℃, the pre-oxidation time is 1.5~2.5 hours, and the rate of heating to the pre-oxidation temperature is 0.8~1.2℃ / min; and / or, the carbonization treatment temperature is 600~800℃, the carbonization treatment time is 1.5~2.5 hours, and the rate of heating to the carbonization treatment temperature is 0.8~1.2℃ / min.

[0021] The present invention also provides the application of capsaicin-containing self-crosslinking hydrogels or capsaicin-containing self-crosslinking hydrogel-based carbon materials in the adsorption of organic dyes, as described in the above technical solution.

[0022] Compared with the prior art, the present invention has the following advantages and technical effects:

[0023] This invention first prepared a capsaicin-functionalized crosslinking agent via Friedel-Crafts alkylation, and then used this agent to synthesize a self-crosslinking hydrogel with high adsorption capacity (AA / TA / SA@CSCA). This self-crosslinking hydrogel achieved maximum adsorption capacities of 22555 mg / g for crystal violet and 5934 mg / g for malachite green. Furthermore, this invention obtained a hydrogel-based carbon material by carbonizing the capsaicin-containing self-crosslinking hydrogel. This hydrogel-based carbon material maintained its high adsorption capacity for crystal violet while significantly increasing its adsorption capacity for malachite green to 14789 mg / g, further enhancing the adsorption performance of the hydrogel material. In addition, this hydrogel-based carbon material can be desorbed and recycled in ethanol, effectively avoiding the secondary pollution problems associated with existing hydrogel materials during acid / alkali desorption processes. Attached Figure Description

[0024] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0025] Figure 1 Microscopic morphology image of AA / TA / SA@24DA prepared in Example 1;

[0026] Figure 2 Infrared absorption spectra of AA@MBA prepared in Comparative Example 1 and AA / TA / SA@CSCA prepared in Examples 1-5;

[0027] Figure 3 Microscopic morphology image of C-AA / TA / SA@24DA prepared in Example 6;

[0028] Figure 4 Standard working curves for crystal violet and malachite green;

[0029] Figure 5 The adsorption performance test results are for AA@MBA prepared in Comparative Example 1 and AA / TA / SA@CSCA prepared in Examples 1-5, where a is the adsorption amount and b is the removal rate.

[0030] Figure 6 The adsorption kinetics curves (a) and adsorption amount changes (b) of AA / TA / SA@24DA prepared in Example 1 at different temperatures.

[0031] Figure 7 The adsorption effect of C-AA / TA / SA@24DA prepared in Example 6 on the two dyes (a) and the change in adsorption effect during recycling (b);

[0032] Figure 8The images show the physical samples of crystal violet and malachite green after adsorption and cyclic adsorption using C-AA / TA / SA@24DA prepared in Example 6. Detailed Implementation

[0033] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0035] This invention provides a capsaicin-containing self-crosslinking hydrogel, the structural formula of which is:

[0036] ;

[0037] R1, R2, R3, and R4 are independently selected from H, -OH, or -COOH; x is 2 to 10, y is 20 to 100, and z is 2 to 10.

[0038] The self-crosslinking hydrogel containing capsaicin functional structure provided by this invention introduces monosubstituted capsaicin functional structure monomers containing carboxyl and sulfonic acid groups into an acrylic acid system, and uses a disubstituted capsaicin functional structure monomer with both polyhydroxy and carboxyl groups as a crosslinking agent. Through free radical polymerization, a self-crosslinking hydrogel with multiple adsorption sites is successfully constructed, which greatly improves the adsorption capacity and efficiency of the hydrogel.

[0039] This invention provides a method for preparing the capsaicin-containing self-crosslinking hydrogel, comprising the following steps:

[0040] (1) Dissolve acidic aromatic compounds and N-hydroxymethylacrylamide in an organic solvent, then add concentrated sulfuric acid dropwise, and obtain a crosslinking agent (CSCA) with capsaicin functional structure through Friedel-Crafts alkylation reaction.

[0041] (2) Acrylic acid (AA), 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid (TA) and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid (SA) are dissolved in water, and then the neutralization degree of the solution is adjusted. Then an initiator and a crosslinking agent of the capsaicin functional structure are added, and the mixture is reacted in a water bath to obtain the capsaicin-containing self-crosslinking hydrogel (AA / TA / SA@CSCA).

[0042] In a preferred embodiment, in step (1), the acidic aromatic compound is selected from 2,4-dihydroxybenzoic acid, 2,6-dihydroxybenzoic acid, 3,5-dihydroxybenzoic acid, gallic acid, or pyrogallic acid, and is more preferably 2,4-dihydroxybenzoic acid. This invention uses aromatic compounds possessing both polyhydroxy and carboxyl groups, or having polyhydroxy groups, to synthesize a cross-linking functional monomer of disubstituted capsaicin by Friedel-Crafts alkylation reaction with N-hydroxymethylacrylamide.

[0043] In a preferred embodiment, when the acidic aromatic compound is 2,4-dihydroxybenzoic acid, the structural formula of the crosslinking agent for the capsaicin functional structure is as follows: When the acidic aromatic compound is 2,6-dihydroxybenzoic acid, the structural formula of the crosslinking agent for the capsaicin functional structure is as follows: When the acidic aromatic compound is 3,5-dihydroxybenzoic acid, the structural formula of the crosslinking agent for the capsaicin functional structure is as follows: When the aromatic acid compound is gallic acid, the structural formula of the crosslinking agent for the capsaicin functional structure is as follows: When the acidic aromatic compound is pyrogallol, the structural formula of the crosslinking agent for the capsaicin functional structure is: .

[0044] In a preferred embodiment, in step (1), the molar ratio of the acidic aromatic compound and N-hydroxymethylacrylamide is 1:(2~3), and more preferably 1:2.4.

[0045] In a preferred embodiment, in step (1), the organic solvent is selected from ethanol; based on the amount of acidic aromatic compound used being 0.1 mol, the amount of ethanol used is 80 mL.

[0046] In a preferred embodiment, in step (1), the mass concentration of the concentrated sulfuric acid is 98%; based on the amount of the acidic aromatic compound being 0.1 mol, the amount of the concentrated sulfuric acid is 10 mL; and the dropping rate of the concentrated sulfuric acid is 1 drop / s. The concentrated sulfuric acid in this invention serves as a catalyst.

[0047] In a preferred embodiment, step (1) further includes filtration, washing and recrystallization after the Friedel-Crafts alkylation reaction is completed; the filtration method is vacuum filtration; the washing reagent is deionized water and anhydrous ethanol; the recrystallization reagent is anhydrous ethanol.

[0048] In a preferred embodiment, in step (1), the temperature of the Friedel-Crafts alkylation reaction is 35~40°C, and the time of the Friedel-Crafts alkylation reaction is 2~4 days, more preferably 3 days.

[0049] In a preferred embodiment, in step (2), the molar ratio of acrylic acid, 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid, and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid is 20:(0.5~1.5):(0.3~0.7), more preferably 20:1:0.5. In this invention, 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid provides carboxyl groups, and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid provides sulfonic acid groups, thereby constructing a self-crosslinking hydrogel with multiple adsorption sites.

[0050] In a preferred embodiment, in step (2), the water is deionized water; the amount of water used is to adjust the solid content of the solution to 20%.

[0051] In a preferred embodiment, in step (2), the reagent used to adjust the neutralization degree of the solution is NaOH; based on the amount of acrylic acid used being 0.1 mol, the amount of NaOH used is 0.08 mol.

[0052] In a preferred embodiment, in step (2), the amount of crosslinking agent added to the capsaicin functional structure is 0.15% to 0.25% of the total molar amount of acrylic acid, 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid, more preferably 0.2%.

[0053] In a preferred embodiment, in step (2), the amount of the initiator added is 0.04% to 0.06% of the total molar amount of acrylic acid, 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid, more preferably 0.05%; the initiator is 2,2'-azobisisobutylamidine dihydrochloride (AIBA).

[0054] In a preferred embodiment, in step (2), the temperature of the water bath reaction is 65~75℃, more preferably 70℃; the time of the water bath reaction is 2.5~3.5 hours, more preferably 3 hours.

[0055] This invention also provides a capsaicin-containing self-crosslinking hydrogel-based carbon material, which is obtained by pre-oxidation and carbonization of the capsaicin-containing self-crosslinking hydrogel described in the above-mentioned technical solution. This invention obtains a hydrogel-based carbon material by pre-oxidizing and carbonizing the capsaicin-containing self-crosslinking hydrogel, further improving the adsorption performance of the hydrogel material. The obtained hydrogel-based carbon material can be desorbed and recycled in ethanol, effectively avoiding the secondary pollution problem of existing hydrogel materials during acid / alkali desorption processes.

[0056] In a preferred embodiment, the pre-oxidation temperature is 180~220℃, more preferably 180~200℃; the pre-oxidation time is 1.5~2.5 hours, more preferably 1.5~2 hours; and the rate of heating to the pre-oxidation temperature is 0.8~1.2℃ / min, more preferably 0.8~1℃ / min. This invention transforms the originally thermoplastic capsaicin-containing self-crosslinked hydrogel into a heat-resistant and stable structure through pre-oxidation, avoiding melting, decomposition, or combustion during the subsequent high-temperature carbonization process, thus ensuring its smooth conversion into a carbon material.

[0057] In a preferred embodiment, the carbonization temperature is 600~800℃, more preferably 600~700℃; the carbonization time is 1.5~2.5 hours, more preferably 1.5~2 hours; and the rate of heating to the carbonization temperature is 0.8~1.2℃ / min, more preferably 0.8~1℃ / min.

[0058] The present invention also provides the application of capsaicin-containing self-crosslinking hydrogels or capsaicin-containing self-crosslinking hydrogel-based carbon materials in the adsorption of organic dyes, as described in the above technical solution.

[0059] In a preferred embodiment, the organic dyes include crystal violet (CV) and malachite green (MG).

[0060] In this embodiment of the invention, room temperature refers to "25±2℃".

[0061] Unless otherwise specified, all raw materials used in the embodiments of this invention were purchased through commercial channels.

[0062] Examples 1-5

[0063] A method for preparing a capsaicin-containing self-crosslinking hydrogel (AA / TA / SA@CSCA), the specific steps of which are as follows:

[0064] (1) Preparation of CSCA

[0065] Raw materials: 2,4-dihydroxybenzoic acid (AR), 2,6-dihydroxybenzoic acid (AR), 3,5-dihydroxybenzoic acid (AR), gallic acid (AR), pyrogallol (AR), N-hydroxymethylacrylamide (industrial grade), concentrated sulfuric acid (98%), ethanol, deionized water;

[0066] Preparation process: Weigh 0.1 mol of 2,4-dihydroxybenzoic acid (Example 1), 2,6-dihydroxybenzoic acid (Example 2), 3,5-dihydroxybenzoic acid (Example 3), gallic acid (Example 4) or pyrogallol (Example 5), and 0.24 mol of N-hydroxymethylacrylamide, respectively, and dissolve them in 80 mL of ethanol. Start an electric stirrer to stir evenly. Place 10 mL of concentrated sulfuric acid in a constant pressure funnel, and then slowly add it to the above reaction system at a rate of 1 drop / s. After the concentrated sulfuric acid is added, start the heating device. The temperature was set at 38℃ and the reaction was carried out for 3 days. The reaction progress was monitored by thin-layer chromatography. After the reaction was completed, the solution was cooled to room temperature and filtered. The filter cake was washed alternately with deionized water and anhydrous ethanol until the filtrate was neutral. The obtained white crude product was recrystallized in anhydrous ethanol to obtain CSCA-1 (24DA, Example 1), CSCA-2 (26DA, Example 2), CSCA-3 (35DA, Example 3), CSCA-4 (345TA, Example 4) and CSCA-5 (456TA, Example 5), respectively.

[0067] The structural formulas for CSCA-1 to CSCA-5 are as follows:

[0068] .

[0069] (2) Preparation of AA / TA / SA@CSCA

[0070] Raw materials: Acrylic acid (AA), 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid (TA), 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid (SA), sodium hydroxide (AR), 2,2'-azobisisobutylamidine dihydrochloride (AIBA) (AR), CSCA, deionized water;

[0071] Preparation process: Weigh 7.2g of AA, add 1.26g of TA and 0.977g of SA according to the molar ratio of AA:TA:SA = 20:1:0.5, and add 37.75g of deionized water to maintain the solid content of the solution at 20%. After the three monomers are completely dissolved, add 3.2g (0.08mol) of NaOH to adjust the neutralization of the solution. Then add 0.064g, 0.064g, 0.064g, 0.064g, 0.0672g, and 0.0584g of CSCA-1, CSCA-2, CSCA-3, CSCA-4, and CSCA-4, respectively. CSCA-5 (CSCA accounts for 0.2% of the total molar amount of the three monomers) and 0.014 g of initiator AIBA (accounting for 0.05% of the total molar amount of the three monomers) were mixed. The solution was then placed in a constant temperature water bath at 70°C and reacted for 3 hours to obtain AA / TA / SA@24DA (Example 1), AA / TA / SA@26DA (Example 2), AA / TA / SA@35DA (Example 3), AA / TA / SA@345TA (Example 4), and AA / TA / SA@456TA (Example 5).

[0072] The structural formulas of AA / TA / SA@CSCA obtained in Examples 1 to 5 are as follows: , x is 4, y is 80, z is 2; in AA / TA / SA@24DA, R1=-OH, R2=H, R3=-COOH, R4=-OH; in AA / TA / SA@26DA, R1=H, R2=-OH, R3=-COOH, R4=-OH; AA / TA / SA@35DA In R1=-COOH, R2=-OH, R3=H, R4=-OH; in AA / TA / SA@345TA, R1=-COOH, R2=-OH, R3=-OH, R4=-OH; in AA / TA / SA@456TA, R1=H, R2=-OH, R3=-OH, R4=-OH.

[0073] Comparative Example 1

[0074] A method for preparing AA@MBA, the specific steps of which are as follows:

[0075] Weigh 7.2g of AA and add 28.8g of deionized water to maintain a solid content of 20%. After the AA is completely dissolved, add 3.2g of NaOH to adjust the neutralization of the solution. Then add 0.0308g of crosslinking agent CSCA-1 and 0.01g of initiator AIBA. Place the solution in a 70℃ constant temperature water bath for 3 hours to finally obtain AA@MBA.

[0076] Figure 1 Microscopic morphology image of AA / TA / SA@24DA prepared in Example 1. From Figure 1As can be seen, the AA / TA / SA@24DA prepared in Example 1 exhibits a three-dimensional network structure under a scanning electron microscope.

[0077] Figure 2 Infrared absorption spectra of AA@MBA prepared in Comparative Example 1 and AA / TA / SA@CSCA prepared in Examples 1-5. From... Figure 2 As can be seen, the AA / TA / SA@CSCA prepared in Examples 1-5 can withstand temperatures up to approximately 1500 cm⁻¹. -1 The benzene ring absorption peak at 3500 cm⁻¹ and 3500 cm⁻¹ -1 The broadening of the absorption peaks of the nearby carboxyl / sulfonic acid groups indicates that the functional monomer of capsaicin has been successfully introduced.

[0078] Example 6

[0079] A method for preparing a capsaicin-containing self-crosslinking hydrogel-based carbon material (C-AA / TA / SA@CSCA) includes the following steps:

[0080] The AA / TA / SA@24DA prepared in Example 1 was placed in a crucible and heated to 200°C at a heating rate of 1°C / min. The temperature was maintained at this temperature for 2 hours to complete the pre-oxidation. After cooling to room temperature, the temperature was increased to 700°C at the same rate under a nitrogen atmosphere for carbonization treatment. After 2 hours, the target product C-AA / TA / SA@24DA was obtained.

[0081] Figure 3 Microscopic morphology image of C-AA / TA / SA@24DA prepared in Example 6. From Figure 3 It can be seen that the C-AA / TA / SA@24DA prepared in Example 6 exhibits a honeycomb structure.

[0082] Adsorption experiments and tests:

[0083] 1. Establishment of standard curves for organic dyes

[0084] Reagents: Crystal violet (CV), malachite green (MG), deionized water.

[0085] The absorbance of crystal violet and malachite green dye solutions was detected using a SpectraMax m2e microplate reader. The specific method is as follows: The dyes were dissolved in deionized water to prepare a 2 g / L stock solution, which was stored under light-protected conditions. Using this stock solution as the starting solution, a series of standard working solutions with concentrations of 20 mg / L, 40 mg / L, 50 mg / L, 100 mg / L, and 200 mg / L were prepared using a serial dilution method. For absorbance detection, a transparent flat-bottomed 96-well microplate was used. 200 µL of the corresponding concentration of standard solution was added to each well, with 2-3 replicates. A zero-concentration blank well was also included on the same plate as a reference. After loading, the plate was gently shaken to mix the liquid and allowed to stand to eliminate air bubbles. The microplate was placed in the microplate reader, and the absorbance of each well was read at 25°C and at an appropriate wavelength. The detection wavelength for crystal violet was 585 nm, and the detection wavelength for malachite green was 619 nm. After blank subtraction, the obtained data were used to plot a standard curve using the absorbance values ​​of the standard series. A linear regression was then used to establish the correlation between concentration and absorbance, resulting in the standard working curve for the dye. The results are shown in [Figure number missing]. Figure 4 .

[0086] Figure 4 Standard working curves for crystal violet and malachite green. From Figure 4 It can be seen that the standard working curve for crystal violet (CV) is Y = 0.01438X + 0.03857, R 2 =0.99989; the standard working curve for malachite green (MG) is Y=0.02125X+0.01677, R 2 =0.99965.

[0087] 2. Adsorption test

[0088] Reagents: AA / TA / SA@CSCA, C-AA / TA / SA@CSCA, AA@MBA.

[0089] Weigh 5 mg (crystal violet) or 10 mg (malachite green) of AA / TA / SA@CSCA, C-AA / TA / SA@CSCA, or AA@MBA sample and place it in a solution containing 2 g / L crystal violet or 1 g / L malachite green dye. The pH of the solution should be 7.8. The initial treatment volume is 40 mL, and the volume is increased by 10 mL each time until the maximum adsorption capacity is reached. Seal the container with plastic wrap and place it in a constant temperature shaking incubator at 25°C and 150 rpm. After 5 hours of treatment, remove the sample and filter it through a Φ25 mm, 0.22 µm polyethersulfone filter. Then, pipette 20 µL of the dye solution into a 96-well microplate and dilute it 10-fold with 180 µL of deionized water. If the concentration is too high, it can be further diluted to 100-fold. The absorbance test of the dye is conducted using the same method as the absorbance test method used in establishing the standard curve for the aforementioned organic dyes. Substituting the obtained dye absorbance into the standard working curve of the dye obtained above, the adsorption equilibrium concentration C of the dye is obtained. e .

[0090] 3. Calculation of adsorption capacity and removal rate

[0091] Let the initial concentration of the dye be C0, and the adsorption equilibrium concentration be C. e The amount of adsorbent used is m, and the volume of the treated liquid is v. Calculate the adsorption capacity Q of the adsorbent using the following formula. e (mg / g) and dye removal rate η (%):

[0092] ;

[0093] .

[0094] 4. Desorption and recycling of C-AA / TA / SA@CSCA

[0095] The adsorbed C-AA / TA / SA@CSCA sample was placed in a mixed solution of ethanol and water (volume ratio of ethanol to water is 7:3) and sonicated at 45°C for 30 minutes to ensure complete desorption of the dye. The solution was removed by filtration and the resulting filter cake was dried for subsequent use.

[0096] 5. Experimental Results

[0097] Figure 5 The adsorption performance test results are for AA@MBA prepared in Comparative Example 1 and AA / TA / SA@CSCA prepared in Examples 1-5, where a is the adsorption amount and b is the removal rate. Figure 5It can be seen that, compared with AA@MBA, the introduction of capsaicin functional monomers in Examples 1-5 significantly improved the adsorption capacity of the materials. Specifically, the AA / TA / SA@24DA prepared in Example 1 achieved adsorption capacities of 22555 mg / g for crystal violet and 5934 mg / g for malachite green, with removal rates of 93.98% and 98.93%, respectively.

[0098] Figure 6 The adsorption kinetics curves (a) and adsorption amount changes (b) of AA / TA / SA@24DA prepared in Example 1 at different temperatures. Figure 6 Part (a) shows the adsorption kinetics curves of AA / TA / SA@24DA in the range of 298~318K. It can be seen that AA / TA / SA@24DA can complete the adsorption of most dyes in about 1 hour, and the higher the temperature, the faster the adsorption efficiency. Figure 6 Part (b) shows the adsorption capacity variation of AA / TA / SA@24DA in the pH range of 2 to 10. It can be seen that, except for a slight decrease in adsorption capacity at pH 2 to 4, the material can meet the adsorption requirements in most pH environments.

[0099] Figure 7 The adsorption effect of C-AA / TA / SA@24DA prepared in Example 6 on the two dyes (a) and the change in adsorption effect during recycling (b). From Figure 7 As can be seen from part (a), the adsorption capacity of C-AA / TA / SA@24DA for crystal violet and malachite green dyes reached 15892 mg / g and 14789 mg / g, respectively, with removal rates of 99.32% and 92.43%, respectively. Figure 7 Part (b) shows that after three desorption cycles, the adsorption capacity of the material for crystal violet and malachite green dyes remained above 14,000 mg / g.

[0100] Figure 8 Images show the physical samples of crystal violet and malachite green after adsorption and cyclic adsorption using C-AA / TA / SA@24DA prepared in Example 6. Figure 8 It can be seen that although the concentration of the remaining dye increases with the number of cycles, it still maintains a good adsorption effect.

[0101] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A self-crosslinking hydrogel containing capsaicin functional structure, characterized in that, The structural formula of the capsaicin-containing self-crosslinking hydrogel is: ; R1, R2, R3, and R4 are independently selected from H, -OH, or -COOH; x is 2 to 10, y is 20 to 100, and z is 2 to 10.

2. A method for preparing the capsaicin-containing functional self-crosslinking hydrogel according to claim 1, characterized in that, Includes the following steps: (1) Dissolve acidic aromatic compounds and N-hydroxymethylacrylamide in an organic solvent, then add concentrated sulfuric acid dropwise, and obtain a crosslinking agent with capsaicin functional structure through Friedel-Crafts alkylation reaction; (2) Dissolve acrylic acid, 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid in water, then adjust the neutralization of the solution, and then add an initiator and a crosslinking agent of the capsaicin functional structure. After water bath reaction, the self-crosslinking hydrogel containing the capsaicin functional structure is obtained.

3. The preparation method according to claim 2, characterized in that, In step (1), the acidic aromatic compound is selected from 2,4-dihydroxybenzoic acid, 2,6-dihydroxybenzoic acid, 3,5-dihydroxybenzoic acid, gallic acid or pyrogallic acid.

4. The preparation method according to claim 2, characterized in that, In step (1), the molar ratio of the acidic aromatic compound and N-hydroxymethylacrylamide is 1:(2~3).

5. The preparation method according to claim 2, characterized in that, In step (1), the temperature of the Friedel-Crafts alkylation reaction is 35~40℃, and the time of the Friedel-Crafts alkylation reaction is 2~4 days.

6. The preparation method according to claim 2, characterized in that, In step (2), the molar ratio of acrylic acid, 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid is 20:(0.5~1.5):(0.3~0.7); the amount of crosslinking agent added to the capsaicin functional structure is 0.15%~0.25% of the total molar amount of acrylic acid, 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid; and the amount of initiator added is 0.04%~0.06% of the total molar amount of acrylic acid, 5-(acrylamide methyl)-2,3,4-trihydroxybenzoic acid and 3-(acrylamide methyl)-5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid.

7. The preparation method according to claim 2, characterized in that, In step (2), the temperature of the water bath reaction is 65~75℃ and the time of the water bath reaction is 2.5~3.5 hours.

8. A self-crosslinking hydrogel-based carbon material containing capsaicin functional structure, characterized in that, The capsaicin-containing functional structure self-crosslinking hydrogel-based carbon material is obtained by pre-oxidation and carbonization treatment of the capsaicin-containing functional structure self-crosslinking hydrogel according to claim 1.

9. The capsaicin-containing functional self-crosslinking hydrogel-based carbon material according to claim 8, characterized in that, The pre-oxidation temperature is 180~220℃, the pre-oxidation time is 1.5~2.5 hours, and the heating rate to the pre-oxidation temperature is 0.8~1.2℃ / min; and / or, The carbonization treatment temperature is 600~800℃, the carbonization treatment time is 1.5~2.5 hours, and the rate of heating to the carbonization treatment temperature is 0.8~1.2℃ / min.

10. The application of a capsaicin-containing self-crosslinking hydrogel as described in claim 1 or a capsaicin-containing self-crosslinking hydrogel-based carbon material as described in any one of claims 8 to 9 in the adsorption of organic dyes.

Citation Information

Cited By

  • Porous carbon material for adsorbing heavy metals as well as preparation method and application of porous carbon material

    CN122006665A

  • A porous carbon material for adsorbing heavy metals and a preparation method and application thereof

    CN122006665B